Nordic welfare cities : negotiating urban citizenship since 1850 - Linnarsson, Magnus; Hallenberg, Mats, 1962- (New York, NY : Routledge, 2024)
"This book examines Nordic cities from 1850 and their transformation from traditional, oligarchic towns to modern, inclusive welfare cities. In the contemporary world, the role of cities as hotbeds for progressive change has become increasingly topical. Historical studies on how Nordic cities addressed social and environmental questions a hundred years ago and how they eventually created new and inclusive policies for the future is a useful contribution to the current debate. The concept of the welfare city is addressed and elaborated upon to analyse the attempts by urban authorities to solve the problems following industrialisation and urbanisation. From the late nineteenth century, municipal public services promoted the integration of new groups in the urban community including workers, immigrants, women and children. The contributions in this book analyse various examples of welfare and public services that include infrastructure and transport systems, health care, housing conditions, outdoor life and entertainment. The chapters highlight the arguments and considerations promoting welfare policies, while also addressing differences between the Nordic countries. The evolution of the Nordic welfare city was a process of several overlapping phases or dimensions. This volume will be of value to students and scholars alike interested in urban history, social and cultural history and European history"--
Keywords: Urbanization -- Scandinavia -- History; Urban policy -- Scandinavia -- History; Public welfare -- Scandinavia -- History; Municipal services -- Scandinavia -- History; Scandinavia -- Social policy; HISTORY / Europe / Scandinavia; HISTORY / Modern / General; HISTORY / Social History